2005
DOI: 10.4049/jimmunol.175.12.7973
|View full text |Cite
|
Sign up to set email alerts
|

The Sphingosine 1-Phosphate Receptor Agonist FTY720 Differentially Affects the Sequestration of CD4+/CD25+ T-Regulatory Cells and Enhances Their Functional Activity

Abstract: The sphingosine 1-phosphate (S1P) receptor agonist FTY720 is well known for its immunomodulatory activity, sequestering lymphocytes from blood and spleen into secondary lymphoid organs and thereby preventing their migration to sites of inflammation. Because inflammation is critically dependent on a balance between Ag-specific Th/effector cells and T-regulatory cells, we investigated the effect of FTY720 on T-regulatory cell trafficking and functional activity. An increased number of CD4+/CD25+ T cells was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
105
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 40 publications
5
105
0
3
Order By: Relevance
“…The fact that FTY720 did not change the expression of GITR as well as the point that GITR seems to be constitutively expressed on CD4 ϩ CD25 ϩ Treg might again underline our hypothesis that FTY720 directly alters the functional activity of CD4 ϩ CD25 ϩ Treg. Still, we consider that this direct impact on CD4 ϩ CD25 ϩ Treg function might additionally be facilitated by a differently regulated sequestration of CD4 ϩ CD25 ϩ Treg vs inflammatory effector T cells resulting in a higher ratio of Treg/effector cells in blood and inflammatory sites (25,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that FTY720 did not change the expression of GITR as well as the point that GITR seems to be constitutively expressed on CD4 ϩ CD25 ϩ Treg might again underline our hypothesis that FTY720 directly alters the functional activity of CD4 ϩ CD25 ϩ Treg. Still, we consider that this direct impact on CD4 ϩ CD25 ϩ Treg function might additionally be facilitated by a differently regulated sequestration of CD4 ϩ CD25 ϩ Treg vs inflammatory effector T cells resulting in a higher ratio of Treg/effector cells in blood and inflammatory sites (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, S1P was demonstrated to be required for optimal suppression of effector T cell activities by Treg (25). Additionally another group showed that the S1P mimetic FTY720 differentially affected the recirculation of Treg vs memory effector T cells (26). However, in the latter investigation it was also considered that modulation of migration might not be the end of the story regarding its impact on Treg.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nofer et al (8) have recently reported that FTY720 reduces atherosclerosis in LDL receptor-deficient mice. Other studies have shown the importance of S1P and the S1P1 receptor in modulating T-cell proliferation and homing to lymph nodes (9,10). Furthermore, S1P has recently been shown to regulate lymphocyte egress from peripheral lymph nodes through interaction with the adaptor protein DOCK2 (11).…”
mentioning
confidence: 99%
“…It is known that S1PR is expressed on Treg cells and influences Treg development, maintenance, and suppressor function (22). In addition, it has been reported that S1P1 can block the differentiation of thymic Treg precursors and function of mature Treg cells and affect Treg cell-mediated immune tolerance (17).…”
Section: Discussionmentioning
confidence: 99%